Effects of Interlayer Distance and van der Waals Energy on Electrochemical Activation of Partially Reduced Graphite Oxide. (10th August 2015) - Yoo, Hyun Deog; Jang, Jong Hyun; Cho, Kyeongjae; Zheng, Yongping; Park, Yuwon; Ryu, Ji Heon; Oh, Seung M.
Abstract: Partially reduced graphite oxide (GOpr) inherits expanded interlayer distance from the parent, graphite oxide (GO), and electronic conductivity from the grandparent, graphite. Indebted to the dual properties, GOpr shows unique behavior so-called electrochemical activation in organic electrolytes; when GOpr is polarized over a certain electrode potential, graphitic layers in GOpr are injected by solvated ions and become ion adsorbing sites permanently. Resultant gravimetric or volumetric capacitance (up to 200 F g −1 or 150 F ml −1 ) exceeds that of commercially available activated carbon electrodes for electric double-layer capacitor (EDLC). Previous literatures have reported that larger interlayer distance ( d ) lowers the on-set potential of electrochemical activation of graphitic carbons. However, the reason of this phenomenon has not yet been studied. In this paper, we combined experimental and theoretical approaches to reveal the effect of interlayer distance and van der Waals energy ( U vdW ) on the electrochemical activation of graphitic carbon. More specifically, we compared the energy for the electrochemical activation ( U EA ) and the van der Waals energy with respect to the interlayer distance. For this purpose, we devised an experimental method to measure U EA from cyclic voltammogram, and this method was verified by in-situ electrochemical dilatometry. The theoretical value of U vdW was calculated by semi-empirical density functional theory (DFT) and those experimental and theoretical values were linearly in accordance with each other. This finding signifies that (1) the electrochemical activation of graphitic carbon occurs by overcoming van der Waals energy to expand the interlayer distance, (2) and the on-set potential for electrochemical activation is varied by the interlayer distance because of the different van der Waals energy.